2019
DOI: 10.1177/1084822319883818
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Competence in Home Healthcare Nursing: Disparity, Cost, Regulatory, Accreditation, Ethical, and Practice Issues

Abstract: Home healthcare patients, who are members of minority, marginalized, or vulnerable patient populations, are at risk for healthcare disparities. Inadequate attention to the needs of the many different types of diverse patient populations seen by home health agencies could compromise an agency’s outcome indicators, reimbursement in value-based payment programs and responsibility to deliver equitable quality care. Culturally competent home health nurses may have a role in decreasing disparities and improving pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 68 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…Home healthcare patients are at risk of outcome disparities when they are members of minority, marginalized, or vulnerable patient populations. [1][2][3][4][5][6][7][8][9][10] In the United States, disparities among these high-risk populations have been repeatedly documented across multiple settings. 11 Home health disparities have been associated with adverse events, re-hospitalization, ineffective disease and medication management, poor functional outcomes, and decreased patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Home healthcare patients are at risk of outcome disparities when they are members of minority, marginalized, or vulnerable patient populations. [1][2][3][4][5][6][7][8][9][10] In the United States, disparities among these high-risk populations have been repeatedly documented across multiple settings. 11 Home health disparities have been associated with adverse events, re-hospitalization, ineffective disease and medication management, poor functional outcomes, and decreased patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Disparities may indicate that regulatory, accreditation, and professional standards for high-quality, equitable care are not being met. 4 In addition, disparities cost billions of dollars to the healthcare system and society every year. 18 Disparities are indicators of poor-quality, unequitable care.…”
Section: Introductionmentioning
confidence: 99%
“…8 Therefore, without a deep understanding of the socio-cultural context, it is impossible to define competent HHC. 9 Shahsavari et al 10 revealed that the socio-cultural context is an important factor in the acceptance of the HHC by patients and their families. Hence, professionals cannot provide effective care if they are not sensitive to patients’ socio-cultural values.…”
Section: Introductionmentioning
confidence: 99%
“…11 Indeed, healthcare disparities are associated with inadequate sensitivity to the cultural needs of the minority patients endangering their health and well-being. 9…”
Section: Introductionmentioning
confidence: 99%
“…CCC is needed not only for patients of diverse races and ethnicity but also for patients in other minority and vulnerable groups. Populations whose cultural norms or lifeways differ from the “expected” norms of the majority population (e.g., due to age, gender, sexual orientation, gender identification, socioeconomic status, education, occupation, mental/physical disability, stigmatized diagnoses) also need nurses who can provide CCC to meet their particular health care needs (Narayan, 2020).…”
Section: Introductionmentioning
confidence: 99%